Withdrawal from long‐term use of zopiclone, zolpidem and temazepam may improve perceived sleep and quality of life in older adults with primary insomnia. Issue 3 (3rd December 2018) - Lähteenmäki, Ritva; Neuvonen, Pertti J.; Puustinen, Juha; Vahlberg, Tero; Partinen, Markku; Räihä, Ismo; Kivelä, Sirkka‐Liisa
Abstract: Long‐term use of benzodiazepines or benzodiazepine receptor agonists is widespread, although guidelines recommend short‐term use. Only few controlled studies have characterized the effect of discontinuation of their chronic use on sleep and quality of life. We studied perceived sleep and quality of life in 92 older (age 55‐91 years) outpatients with primary insomnia before and after withdrawal from long‐term use of zopiclone, zolpidem or temazepam (BZDA). BZDA was withdrawn during 1 month, during which the participants received psychosocial support and blindly melatonin or placebo. A questionnaire was used to study perceived sleep and quality of life before withdrawal, and 1 month and 6 months later. 89 participants completed the 6‐month follow‐up. As melatonin did not improve withdrawal, all participants were pooled and then separated based solely on the withdrawal results at 6 months (34 Withdrawers. 55 Nonwithdrawers) for this secondary analysis. At 6 months, the Withdrawers had significantly ( P  < 0.05) shorter sleep‐onset latency and less difficulty in initiating sleep than at baseline and when compared to Nonwithdrawers. Compared to baseline, both Withdrawers and Nonwithdrawers had at 6 months significantly ( P  < 0.05) less fatigue during the morning and daytime. Stress was alleviated more in Withdrawers than in Nonwithdrawers ( P  < 0.05). Satisfaction with life and expected health 1 year later improved ( P  < 0.05) in Withdrawers. In conclusion, sleep disturbances, daytime fatigue and impaired quality of life may resolve within 6 months of BZDA withdrawal. These results encourage withdrawal from chronic use of benzodiazepine‐type hypnotics, particularly in older subjects.